Influence of the imaging method and histopathological features on preoperative size prediction of ductal carcinoma in situ (DCIS) of the breast - Niedźwiecki, Sebastian; Piekarski, Janusz; Jeziorski, Arkadiusz (Menopause Review/Przegląd Menopauzalny, 2013)
Aim of the study: The aim of the study was to evaluate the accuracy of mammography and ultrasonography in predicting preoperative DCIS size compared to final histopathologic measurement of the extent of DCIS. Material and methods: A retrospective analysis was performed of the clinical, histopathological and imaging records of 32 consecutive female patients initially treated by breast-conserving surgery for DCIS between 1999 and 2005. Group 1 consisted of 19 female patients with a palpable breast tumor, while group 2 comprised 13 female individuals with no palpable breast lesion. All patients were preoperatively diagnosed with biopsy. Results: In group 1, mammography size was smaller than histopathological size in 14 patients (73.68%), while they were equal in 5 cases (26.31%). However, in group 2, mammography size was the same as histopathological size in 5 cases (38.46%), but was smaller in 8 individuals (61.53%). The degree of the underestimations for both imaging methods compared to pathological size were identical, with a value of 1.1 ±0.9 cm and 1.2 ±1.1 cm for groups 1 and 2, respectively. Furthermore, in both study groups, as final histopathologic size decreased, the degree of underestimation increased (p < 0.05). Conclusions: The present study demonstrates that smaller DCIS pathological size is associated with greater discrepancies in imaging method size prediction.